How hard is it to remember Bananarama? The perennial forgetting of girls in music. Issue 2 (13th May 2020) - Robinson, Lucy
Abstract : Remembering and forgetting female pop musicians sits within the broader project of feminist and queer identity histories. The history of uncovering a past in order to inform the here and now raises questions about the relationship between lived experiences and the types of history that are produced. There is an assumption that each may inform the other. In the 1980s, within the academy, there was a growing understanding of the importance of remembering and re-remembering marginalized agents. This sat alongside an increasing visibility of the girl, both as a market and as a performer. Looking at the discourses, remembering and forgetting, seeing and silencing of the successful girl band Bananarama, I will map the active levels through which female performers have been marginalized, have resisted and persisted. I ask: what will it take for them to be remembered?